Socialization and Training on the Utilization of Cabbage Waste as the Main Material for Making Liquid Organic Fertilizer (Poc) in Talimbaru Village, Barusjahe District, Karo Regency - Ginting, Agus Susanto; Sinuhaji, Ferdinand; Tarigan, Sumatera; Tarigan, Nicolas Jovi (PT FORMOSA CENDEKIA GLOBAL, 2025)
Talimbaru Village is one of the villages in Barusjahe District, Karo Regency. This village is one of the centers for producing cabbage (Cabbage) plants. The cabbage waste produced has not been utilized and is usually only thrown away or left behind on agricultural land. The fermentation process of cabbage waste can be converted into liquid organic fertilizer (POC) which can be used to improve the soil and can be a useful nutrient for plant growth. This service activity aims to provide training in making liquid organic fertilizer to farmer groups with materials in the form of cabbage waste as the main ingredient and coconut water, clean water, yeast, brown sugar and EM-4 as decomposer liquid. The results of this activity were in the form of high response and enthusiasm of participants in participating in socialization and training and obtaining leachate that can be diluted as a soil amendment and nutrients for plant growth.